The dangers of castor oil tea in neonates in rural Haiti: A case report - Wilhermine Jean Baptiste; Wilhermine Jean Baptiste; Michelucia Casseus; Michelucia Casseus; Alka Dev; Patrice Joseph; Peter F. Wright (Frontiers Media S.A., 2023)
During a 2-year period, eight cases of a distinct illness were seen among 1,424 neonates admitted to a newly established neonatal care unit in southern Haiti. The newborns presented with a picture of sepsis with shock, vomiting, hypotonia, lethargy, and abdominal distention. Five cases proved fatal and another case left the hospital against advice in extremis with little chance of survival. In each case, the illness was associated with a history of ingestion of teas that included castor oil, known as lok in Haitian Creole. The presumptive cause of the illness was established by the presence of a dark, oily substance in drainage from the nares and nasogastric tubes and by subsequent admission on direct questioning of the caregivers, who said that the infants had been given large amounts of lok. The castor oil tea had been given to three infants in the immediate neonatal period where its use is attributed to encouraging the passage of meconium. The five remaining infants were between 15 and 30 days of life when they were given lok shortly before admission to the neonatal unit for treatment of an undefined illness. All of them were term infants with no identified risks at birth. As nasogastric tubes are not routinely placed in sick neonates, and the parents did not volunteer information about lok administration, the practice may be more widespread than that recorded here. Although our data are confined to observations in Haiti, the use of traditional medicines is a globally widespread phenomenon. Attention must be drawn to the potential toxicity of such preparations and means found to ban their use in neonates.